Waste Management in Rivers State: The Role of the Mechanical Engineer - Ovundah King Wofuru-Nyenke; Gift Prince Okere (International Journal of Management and Operations Research, 2025)
This paper discusses various waste management and disposal strategies and the role of the Mechanical Engineer in their implementation. For many decades, different research institutes of many countries, private organisations as well as individuals have been trying to develop or design effective methods of handling the solid wastes generated in their environment. This is because of the conspicuous effects of these wastes which have become a matter of great concern locally, nationally and even globally. The desire to control or handle these solid wastes and their attendant problems led to the different waste management methods which exist today. In spite of the expectations of the masses, cities in Nigeria still grapple with waste management problems, as some areas, particularly the satellite towns stink because of the refuse heaps by the streets and walkways. This paper proposes waste management and disposal strategies such as separation, compaction, shredding or pulverising and incineration, all of which can be aided by design and construction of various machines and equipment by Mechanical Engineers. The paper also proposes a number of maintenance strategies to ensure that waste management equipment and machines do not breakdown too frequently and result in loss of time and money. This research is significant because it proposes effective strategies that can be applied to solve solid waste management and disposal problems, especially in the environs of Rivers State.
Keywords: Waste Management; Waste Disposal; Environment; Machines; Engineering Strategies; Rivers State